Doha scenarios, trade reforms, and poverty in the Philippines: a CGE analysis - Cororaton, Caesar B.; Cockburn, John; Corong, Erwin (International Food Policy Research Institute, 2005)
The paper examines the possible impact of Doha agreement on Philippine poverty. Using a detailed CGE analysis, the agreement is observed to depress world demand for Philippine agricultural exports, and thus slightly increase poverty, especially among rural households. However, an ambitious full trade liberalization scenario, which involves free world trade and domestic liberalization, leads to increased industrial exports that favor urban households. These impacts are driven primarily by domestic trade liberalization, as free world trade favors the agricultural sector by increasing the cost of competing agricultural imports.